The management of infants, children, and youth at risk for hepatitis C virus infection. Issue 7 (11th November 2021) - Bitnun, Ari
Abstract: Hepatitis C virus (HCV) infection affects 0.5% to 1.0% of the Canadian population. Most paediatric HCV infections are a consequence of vertical transmission or, among youth and young adults, the result of engaging in high-risk behaviours, such as injection drug use and unprotected sexual activity. It is now recommended that all infants, children, and youth with one or more risk factors be screened for HCV infection. Treating chronic HCV infection with direct-acting antivirals has been shown to achieve sustained virologic suppression in 97% to 100% of children as young as 3 years old. Paediatricians and family physicians have an important role in educating youth regarding HCV infection risks and prevention, and in advocating to government and public health authorities for comprehensive harm reduction interventions targeting at-risk youth, accessible treatments, and routine prenatal screening for HCV.